Development of a nomogram to predict the risk of hepatocellular carcinoma in patients with hepatitis B-related cirrhosis on antivirals - Shi, Ke; Li, Ping; Zhang, Qun; Zhang, Yi; Bi, Yufei; Zeng, Xuanwei; Wang, Xianbo (Frontiers in Oncology, 2023)
Objective: Patients with compensated hepatitis B-related cirrhosis (HBC) receiving antivirals are at the risk of hepatocellular carcinoma (HCC). This study aimed to develop and validate a nomogram for predicting the incidence of HCC in patients with HBC. Design: A total of 632 patients with compensated HBC treated with entecavir or tenofovir between August 2010 and July 2018 were enrolled. Cox regression analysis was used to identify independent risk factors for HCC and a nomogram was developed using these factors. The area under the receiver operating characteristic curve (AUC), calibration curve, and decision curve analyses were used to evaluate the nomogram performance. The results were validated in an external cohort (n = 324). Results: In the multivariate analysis, age per 10 years, neutrophil–lymphocyte ratio > 1.6, and platelet count < 86×109/L were independent predictors of 3-year HCC occurrence. A nomogram was developed to predict HCC risk using these three factors (ranging from 0 to 20). The nomogram showed better performance (AUC: 0.83) than that of the established models (all P < 0.05). The 3-year cumulative HCC incidences in the low- (scores < 4), medium- (4–10), and high-risk (> 10) subgroups were 0.7%, 4.3%, and 17.7%, respectively, in the derivation cohort, and 1.2%, 3.9%, and 17.8%, respectively, in the validation cohort. Conclusion: The nomogram showed good discrimination and calibration in estimating HCC risk in patients with HBC on antivirals. High-risk patients with a score > 10 points require close surveillance.